Identification and characterization of a perfect mono-nucleotide microsatellite within 16S rRNA gene in chicken mtDNA genome - Shengguo, Z.; Hanotte, Olivier H.; Han Jianlin (2009)
An alignment of 17 complete mitochondrial DNA (mtDNA) sequences of chickens and jungle fowls revealed a perfect mono-nucleotide microsatellite repeat unit consisting of between 8 and 13 Cs within the 16S rRNA gene in nine samples. However, the remaining eight sequences had three kinds of interrupted non-polymorphic fragments – (C)4T(C)5, (C)4T(C)6 and (C)4T(C)3TC) – within the same region. To characterize this microsatellite, 344 samples of indigenous and commercial chicken populations as well as wild red jungle fowls were genotyped. Thirty-five samples were further sequenced for the same region. Both genotyping and sequencing results confirmed the presence of these two types of structures in chicken mtDNA genome while the wild red jungle fowl samples only possessed one of the interrupted fragments, (C)4T(C)5. Among the chickens analyzed, the two structures showed a clear pattern of geographic distribution. The perfect repeats were mainly detected in indigenous chickens from West Asia including Bangladesh, Myanmar and Pakistan and in the majority of commercial chickens. The interrupted fragment, also (C)4T(C)5, occurred predominantly among indigenous chickens from South and Southeast Asia including China, Korea and Papua New Guinea. This polymorphic mono-nucleotide microsatellite, the first of its kind being validated in the avian mitochondrial genome, could be useful in providing insights into the evolutionary mechanism of polymorphism and/or instability of mtDNA microsatellites and also into a better estimation of the mutation rate of such microsatellites in birds.